Global modeling of NF3 line positions and intensities from far to mid-infrared up to 2200 cm−1. (December 2019) - Egorov, Oleg; Nikitin, Andrei; Rey, Michäel; Rodina, Alena; Tashkun, Sergei; Tyuterev, Vladimir
Highlights: First global combined line list for NF3 up to 2200 cm −1 was constructed. An effective operator method was combined with ab initio variational calculations. Detailed validations using experimental data from PNNL are reported. Abstract: In this work we report first global modeling of NF3 line positions and intensities up to the Tetradecad range of interacting bands (< 2200 cm −1 ). The calculations are based on our ab initio potential energy and dipole moment surfaces of NF3 which are used to compute initial theoretical line lists. The technique of six order contact transformations was then employed to build a global effective model for vibrational polyads. The purely theoretical parameters of this effective Hamiltonian were refined by fitting to assigned experimental line positions. The parameters of the effective dipole moment of vibrational bands were determined by fitting to our ab initio line intensities. The resulting global combined line list contains 41 cold and 683 hot sub-bands. It can be used for accurate simulating of NF3 radiative properties in the range 0–2200 cm −1 . The theoretical simulations of absorption were compared and validated to the experimental database of Pacific Northwest National Laboratory.